Modern applications of hibah in the light of shari'ah objectives of gift and donation contracts (al-tabarru'at) - Ali, Mohammed Farid (Center for Islamic Sciences, 2015)
After presenting the Sharīʿah objectives of both tabarruʿāt and hibah briefly, this paper looks at the applications of hibah as a “supporting Sharīʿah concept” in four contracts proposed to the Shariah Advisory Council of Bank Negara Malaysia (SAC). The four contracts are (1) Interbank Mudarabah Investment Contract, (2) al-Ijarah thumma-l-Bayʿ Contract, (3) Wadiʿah Contract, and (4) Qarḍ Contract. Do these modern applications of hibah realize the maqāṣid of al-tabarruʿāt and hibah? Beside positive maqāṣid, the paper also looks into instances in which hibah is utilized to serve purposes which are negative in nature such as ribāʾ and bribery (rishwah). Based on the maqasidic approach to tabarruʿāt and hibah, the paper recommends terms and conditions when combining hibah with other transactions and contracts. These conditions will seek to overcome the violation of the original maqāṣid of the hibah and tabarruʿāt.